Pengelolaan Keuangan Keluarga Dan Pengenalan Dasar-Dasar Investasi Menuju Keluarga Mandiri Bagi Ibu-Ibu Majlis Taklim Al Auladiyah Di Kelurahan Bakti Jaya Kecamatan Setu Tangerang Selatan - Tsarina Zenabia; Endah Finatariani; Setianingsih Setianingsih; Anisa Anisa; Tubagus Arya Abdurachman (S1 Accounting Program, Universitas Pamulang, 2020)
Pengabdian Kepada Masyarakat (PKM) which is called Community Service Activities was held from 6-8 July 2020 as a form to fulfilling the obligations of the higher education of Tri Dharma at Pamulang University. The purpose of this PKM is to Introduce Fundamental Investment and Financial Management Towards Independent Family For Majelis Taklim Al Auladiyah in Tangerang Selatan. Financial management for the family is needed so, therefore, all family needs such as food, clothes, shelter, school fee, or desire to buy a new motorbike/car can be fulfilled. First things first are getting to know your financial condition, and determine your needs not to wants, and choose top priority, the family has to prepare a household budget for current and future needs avoids unnecessary desires, and don’t “Big Pegs than the Pole” neither. One of the stages of financial family planning is preparing a household budget to prevent financial failure in the household. The result or output of this activity is to increase knowledge of the importance of understanding, financial arrangements, improve family welfare to avoid dependence on borrowing money from creditors.